The role of the Nrf2/GSH antioxidant system in cisplatin resistance in malignant rhabdoid tumours - Hannon Barroeta, Patricia; O’Sullivan, Maureen J.; Zisterer, Daniela M. (Journal of cancer research and clinical oncology, 2023)
Purpose Malignant rhabdoid tumour (MRT) is a rare and aggressive childhood malignancy that occurs in the kidneys or central nervous system and is associated with very poor prognosis. Chemoresistance is a major issue in the treatment of this malignancy leading to an urgent need for a greater understanding of its underlying mechanisms in MRT and novel treatment strategies for MRT patients. The balance between oxidative stress mediated by reactive oxygen species (ROS) and the antioxidant system has become a subject of interest in cancer therapy research. Studies have implicated key players of the antioxidant system in chemotherapeutic including the well-known antioxidant glutathione (GSH) and the transcription factor nuclear erythroid-related factor-2 (Nrf2). Methods This study evaluated the role of these components in the response of MRT cells to treatment with the commonly used chemotherapeutic agent, cisplatin. Results This study characterised the basal levels of GSH, ROS and Nrf2 in a panel of MRT cell lines and found a correlation between the expression profile of the antioxidant defence system and cisplatin sensitivity. Results showed that treatment with ROS scavenger N-acetylcysteine (NAC) protected cells from cisplatin-induced ROS and apoptosis. Interestingly, depleting GSH levels with the inhibitor buthionine sulphoximine (BSO) enhanced cisplatin-induced ROS and sensitised cells to cisplatin. Lastly, targeting Nrf2 with the small molecule inhibitor ML385 or by siRNA diminished GSH levels, enhanced ROS and sensitised resistant MRT cells to cisplatin. Conclusions These results suggest that targeting the Nrf2/GSH antioxidant system may present a novel therapeutic strategy to combat chemoresistance in rhabdoid tumours.